(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
The multifaceted and complex activity of an educator includes such important tasks as educating the young generation to be polite and attentive, arming them with scientific knowledge. Implementation of these depends on the educator’s various activities: teaching children, organizing and conducting educational activities outside of school and classroom, conducting pedagogical propaganda among parents, etc. All this requires the teacher to have deep knowledge, to love his field and children. This article describes the role of the educator in society.